2014
DOI: 10.1681/asn.2013090993
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mafb in Podocytes Protects against Diabetic Nephropathy

Abstract: We previously showed that the transcription factor Mafb is essential for podocyte differentiation and foot process formation. Podocytes are susceptible to injury in diabetes, and this injury leads to progression of diabetic nephropathy. In this study, we generated transgenic mice that overexpress Mafb in podocytes using the nephrin promoter/enhancer. To examine a potential pathogenetic role for Mafb in diabetic nephropathy, Mafb transgenic mice were treated with either streptozotocin or saline solution. Diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
(73 reference statements)
1
32
0
1
Order By: Relevance
“…In respect to the glomerulus, Mafb KO mice show a quite similar phenotype as Pod1 KO animals, with a severe maturational defect of developing glomeruli and podocytes [145,150]. Interestingly, a more recent study could demonstrate that Mafb overexpression in podocytes ameliorates the course of diabetic nephropathy by stabilization of slit diaphragm molecules like Nephrin, upregulation of antioxidative enzymes and modulation of Notch signaling pathways [151]. These findings might indicate that Mafb-controlled transcriptional networks involve adaptive mechanisms required in disease states.…”
Section: Mafb Tcf21 and Various More Transcription Factors Related Tmentioning
confidence: 91%
“…In respect to the glomerulus, Mafb KO mice show a quite similar phenotype as Pod1 KO animals, with a severe maturational defect of developing glomeruli and podocytes [145,150]. Interestingly, a more recent study could demonstrate that Mafb overexpression in podocytes ameliorates the course of diabetic nephropathy by stabilization of slit diaphragm molecules like Nephrin, upregulation of antioxidative enzymes and modulation of Notch signaling pathways [151]. These findings might indicate that Mafb-controlled transcriptional networks involve adaptive mechanisms required in disease states.…”
Section: Mafb Tcf21 and Various More Transcription Factors Related Tmentioning
confidence: 91%
“…Indeed, MAFB/Kreisler, TCF21/POD1, LMX1B, and the FoxC-class TFs have already been shown to be of relevance in podocytes. [15][16][17][18][19] Frequently, networks of TFs cooperatively control gene expression by binding in TF modules to enhancers. These tissuespecific DNA-regulatory elements are located distally from the TSS.…”
mentioning
confidence: 99%
“…Furthermore, previously described enhancers conferring podocyte-specific gene expression and the TFs bound to these enhancers were recapitulated by our ChIPseq data and motif analysis (Supplemental Figure 7). 8,16,19 Reanalysis of previously published WT1 ChIPseq data from embryonic kidneys, where WT1 is expressed in nephron best matching motifs from public databases are shown on the right with a similarity E value. Promoters are enriched in motifs generally found close to TSS (Ets-class TF, E box, GC box, CCAAT box), whereas enhancers harbor motifs for TFs with established significance in podocytes (Fox-class TFs, Lmx1b, Mafb).…”
mentioning
confidence: 99%
“…Previous studies have shown that some neuronal TFs are expressed also in podocytes, such as Kreisler (MafB) which is involved in both early central nervous system organization and in kidney development [34], regulating also Nephrin promoter activity [35]. NeuroD, a member of helix-loop-helix (bHLH) transcription factor, is a potent regulator of neuron differentiation and survival both at an early and late stage of the central nervous system (CNS) development [36, 37], and genetic mutations of NeuroD gene are associated with severe abnormalities of many neurological functions [38-40].…”
Section: Discussionmentioning
confidence: 99%